1980
DOI: 10.2134/agronj1980.00021962007200050005x
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Deficiency and Toxicity Sensitivities of Soybean Cultivars

Abstract: Soybean [Glycine max (L.) Merr.] cultivars vary in plant growth response to Mn deficiency and toxicity. Cultivar selection for field studies to evaluate responses to Mn deficiency and toxicity is important. The objective of this study was to determine the differential sensitivity of cultivars to Mn deficiency and toxicity prior to regional field studies on the diagnosis and correction of Mn problems in the production of soybeans. For evaluating relative ranking of cultivars sensitive to Mn deficiency, seven so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
2

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 5 publications
(6 reference statements)
1
11
1
2
Order By: Relevance
“…Graham, unpublished data). In contrast to our experience with cereals, Ohki et al (72) found that the Mn content of soybean seeds did not alter the varietal ranking in tolerance to Mn deficiency. Nevertheless, it appears that the genotype of the scion had a dominant role in determining the accumulation of minerals, including Mn, in soybean seeds, and that of the rootstock much less, or nil in the case of Mn (47).…”
Section: Genetic Differences In Internal Redistribution Of M Ncontrasting
confidence: 99%
“…Graham, unpublished data). In contrast to our experience with cereals, Ohki et al (72) found that the Mn content of soybean seeds did not alter the varietal ranking in tolerance to Mn deficiency. Nevertheless, it appears that the genotype of the scion had a dominant role in determining the accumulation of minerals, including Mn, in soybean seeds, and that of the rootstock much less, or nil in the case of Mn (47).…”
Section: Genetic Differences In Internal Redistribution Of M Ncontrasting
confidence: 99%
“…Novais et al (1989) e Ohki et al (1980) também determinaram desempenhos diferenciados entre cultivares de soja, quanto à eficiência na absorção ou utilização de Mn, em condições de disponibilidade limitada do elemento no solo. Evidências quanto às diferenças genotípicas na absorção e utilização de Mn por plantas de soja também foram verificadas por Reddy e Dun (1987).…”
Section: Manganêsunclassified
“…These inconsistencies among species may be attributed in part to the existence of large variations within species in sensitivity to Mn deficiency. Intraspecific variation has been reported for a number of crops including wheat (29,42), barley (43,103), oats (19,103), peas (37), soybeans (105) and lupins (159) and it almost certainly exists in all species (Chapter 17).…”
Section: Plantsmentioning
confidence: 99%